A Curious Case of Dengue Fever: A Case Report of Unorthodox Manifestations - Raja Shakeel Mushtaque; Syed Masroor Ahmad; Rabia Mushtaque; Shahbano Baloch (Case Reports in Medicine)
Dengue is the major cause of arthropod-borne viral disease in the world. It presents with high fever, headache, rash, myalgia, and arthralgia and it is a self-limiting illness. Severe dengue can occur in some cases resulting in dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). We present a case of a 32-year-old male patient of high-grade fever, bilateral subconjunctival hemorrhages, swelling on hands and lips, and nasal bleeding. After investigations, he was diagnosed with dengue fever and it was observed that he developed systemic fungal infection secondary to Candida tropicalis infection. The patient’s bone marrow biopsy showed hemophagocytic activity. He also developed hepatitis E infection while hepatitis A, B, or C serology profile showed no active infection. The bilateral iliopsoas hematoma was also observed on CT scan manifested by decreased power in bilateral lower limbs and pain in the right leg. The patient was treated in the hospital with antibiotics (ceftriaxone 2 g once daily for 14 days) and antifungal (fluconazole 200 mg per oral initially for one day then 100 mg daily for 13 days) medicines, and his condition improved on discharge. There is evidence of variable presentations of dengue fever after the disease burden is increased, and thus, diagnosing with such manifestations can be very challenging.